Study the Effect of Ferula hermonis Extract on HepG2 cell line culture (Journal of the College of Basic Education, 2023)
Ferula hermonis Boiss (Apiaceae) is known in the Midleast as"zallouh". In the last decade, scientists paid attention to study chemistry and biological activity of the plant. In this study Ferulahermonis were collected and evaluated for cytotoxic activity. Theplant was extracted with methanol The cytotoxic effect of theextracts was examined in-vitro on human cell line (Human livercarcinoma cell line HepG2). Results were shown that significantdecrease of HepG2 cells viability. The effect of F. hermonis on cellviability of HepG2 cell line culture show that plant extract causesignificant decrease ( p< 0.05) of HepG2 cell viability, and thisdecrease in cell viability is increased with the increasing the extractconcentrations in comparison with the negative control, and thegrowth inhibition percentage reach to (78.3%).Introduction Ferula hermonis Boiss. (Apiaceae), commonly known as " Shilsh-el-zallouh" , "Hashishat-al-kattira" or "The Lebanese Viagra" ,is asmall perennial shrub that grows abundantly at more than 2500 m onthe high mountain areas of northern Lebanon, and on the biblicalMount Hermon in Southern Lebanon, (El-Taher et al., 2001). MiddleEast herbalists have used the seeds and roots of this plant forcenturies as a folk remedy as an aphrodisiac to treat frigidity inwomen, and erectile and sexual dysfunction in men by increasingblood flow to sexual organs. The antimicrobial activity of the crudeextract and the isolated compounds has been reported (Hilan et al.,2007). Previous phytochemical studies on this plant have revealedthe presence of various sesquiterpenes, mainly of the daucane estertype (Galal et al., 2001). On roots of Ferula hermonis, severalsesquiterpenes have been isolated, most of which display biologicalactivities. The active constituents are believed to be daucane alcohols